Cutaneous Analgesia and Systemic Toxicity of Carbetapentane and Caramiphen in Rats. Issue 1 (1st January 2012) - Hung, Ching-Hsia; Chu, Chin-Chen; Chen, Yu-Chung; Liu, Kuo-Sheng; Chen, Yu-Wen; Wang, Jhi-Joung
Abstract : Background: Caramiphen produces spinal anesthesia; caramiphen and carbetapentane have never been tested as infiltrative cutaneous analgesic. The aim of this study was to compare cutaneous analgesia of caramiphen and carbetapentane with bupivacaine and evaluated their central nervous system and cardiovascular toxicity. Methods: After the blockade of cutaneous trunci muscle reflex with subcutaneous drug injections in rats, we evaluated the local anesthetic effect of carbetapentane and caramiphen on infiltrative cutaneous analgesia. After continuous intravenous infusion of equipotent doses of bupivacaine, carbetapentane, caramiphen, and saline, we observed mean arterial blood pressure and heart rate and monitored the onset time of seizure, apnea, and impending death. Results: Carbetapentane and caramiphen acted like bupivacaine and elicited cutaneous analgesia in a dose-related fashion. On a 50% effective dose (ED50 ) basis, the ranks of potencies were bupivacaine (1.78 [1.52–2.07]) > carbetapentane (2.53 [2.38–2.77]) > caramiphen (3.60 [3.41–3.99]) ( P < 0.01). At equianalgesic doses (ED25, ED50, ED75 ), the duration caused by carbetapentane or caramiphen was similar to that caused by bupivacaine. Under equipotent doses, the infusion time of carbetapentane or caramiphen required to cause seizure, apnea, and impending death was longer than that of bupivacaine ( P < 0.05). The decline in mean arterial blood pressure and heart rate was slower with carbetapentane or caramiphen when compared with bupivacaine ( P < 0.01 for the differences) at equipotent doses. Conclusions: Carbetapentane and caramiphen were similar to bupivacaine at producing durations of cutaneous analgesia but were less likely than bupivacaine to induce central nervous system and cardiovascular systemic toxicity.